Study on the Loess Immersion Test of Metro Line 2 in Xi’an, Shaanxi Province, China - Yuanjun Xu; Jiading Wang; Tianfeng Gu; Dengfei Zhang; Weiqian Ma (Advances in Civil Engineering)
With the implementation of China’s western development and “One Belt, One Road” initiative, there are more and more projects in the collapsibility loess area, and the collapsibility loess problem encountered in the construction is becoming more and more prominent. In this paper, the collapsibility loess of the south extension section of Xi’an Metro Line 2 is investigated, and its collapsibility characteristics are studied through a large-scale site immersion test. The test site was a 15 m diameter circular test pit, which took 35 days for water injection and 60 days for observation after water stopped. The test results showed that the maximum self-weight collapsibility of the soil layer in the test pit is 32 mm, and the deformation amount is 10.05 mm in Q3 and 9.55 mm in Q2. The maximum deformation amount of 32 mm is less than 70 mm in the shallow marker; it may be caused by the paleosol layer as a bridge to provide a support to the overlying soil layer. The shape of the sphere of influence after immersion resembles a trumpet, slightly protruding outwards from the paleosol. The scope of influence between the infiltrated and saturated zones gradually increases with depth, and the saturated zone is generally smaller than the infiltrated zone. The research results of this paper can provide technical support and reference for the construction of Xi’an Metro Line 2 and other related projects in the region.